EFFECT OF ARECA NUT EXTRACTS ON SOME DIGESTIVE ENZYMES IN VITRO (Biological Sciences - PJSIR, 2003)
The Arcea nut extracts (n-hcxanc and methanol) were used on three important digestive enzymes (a-amylase. a-chymotrypsin and lipase) in vitro. The result showed significant reduction of a-amylase activity (between 47-64% inhibition). Whereas, both extracts of Areca produced significant increase in lipase activity (54% and 27%. respectivel y). Significant increase in a-chymotrypsin activity (78%) with 11-hexanc extract and a reduction of ( 18%) with methanol extract were seen.